Requirements engineering : foundation for software quality : 24th International Working Conference, REFSQ 2018, Utrecht, the Netherlands, March 19-22, 2018, Proceedings /: foundation for software quality : 24th International Working Conference, REFSQ 2018, Utrecht, the Netherlands, March 19-22, 2018, Proceedings. (2018) - Unknown
No abstract available